Genetic Studies On The GHSR and IGF1R and Their Relationship With Stunting: A Systematic Literature Review - Saarah Hamidah Asmara Indratno; Jekmal Malau; Ahsanal Kasasiah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Stunting, also known as short stature, is a condition that occurs in children where children grow too short for their age. It can be influenced by several external and internal factors. This study explored various databases including Pubmed, Science Direct, Sage Journal, Springer Link, with keywords: "stunting OR short stature AND GHSR AND IGF1R AND genetic". There are 114 articles that match the PICOTS elements to be further reviewed using the PRISMA diagram. In this review article, 10 research articles published in 2011-2024 were used as sources of information. This review article discusses that internal factors of stunting can be caused by genetic factors influenced by growth genes, one of which is GHSR and IGF1R. Whole genome sequencing revealed potential genes involved in the growth pathway that showed an association between genetic variation in GHSR and IGF with the risk of the body's production or response to growth hormone that causes delayed child growth. The evidence highlights the possibility that these putative genetic markers could offer more effective treatment by focusing on the pathophysiology associated with development stunting. Due to lack of genetic studies on stunting genes carried out in Asian nations, genetic testing has not been used in clinical practice as a routine evaluation in the current national implementation, especially in Indonesia